2023
DOI: 10.1002/cbic.202300163
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical and Computational Approaches to Study Ternary Complexes: A ‘Cooperative Relationship’ to Rationalize Targeted Protein Degradation

Abstract: Degraders have illustrated that compound-induced proximity to E3 ubiquitin ligases can prompt the ubiquitination and degradation of disease-relevant proteins. Hence, this pharmacology is becoming a promising alternative and complement to available therapeutic interventions (e. g., inhibitors). Degraders rely on protein binding instead of inhibition and, hence, they hold the promise to broaden the druggable proteome. Biophysical and structural biology approaches have been the cornerstone of understanding and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 141 publications
(350 reference statements)
0
16
0
Order By: Relevance
“…A second major limitation is that the development of PROTACs is largely empirical, with few generally applicable design rules 9 . As a result, many PROTAC development campaigns fail due to the inability to identify PROTACs that efficiently induce target degradation, and in most cases, these results are not published.…”
Section: Introductionmentioning
confidence: 99%
“…A second major limitation is that the development of PROTACs is largely empirical, with few generally applicable design rules 9 . As a result, many PROTAC development campaigns fail due to the inability to identify PROTACs that efficiently induce target degradation, and in most cases, these results are not published.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to monovalent small molecule drug discovery, there are several levels of increased complexity when designing these larger (>700 Da) and structurally complex modalities that tend to lie beyond the realm of the rule of five (bRo5). , In addition to the POI-L optimization process, successful PROTAC campaigns require exploration of multiple variables, including the type of E3 ligase and E3-L pharmacophore, the linker attachment point to both the POI-L and the E3-L (exit vectors), as well as the linker-length, -morphology, and -polarity. Furthermore, due to the limited structural data on ternary complexes , and the challenges involved in computational approaches, PROTAC hit finding and structure–activity relationship (SAR) exploration within this modality remains mainly empirical. Furthermore, the larger size of these molecules coupled with their intricate architectures demands increased synthetic efforts, further adding to the significant time and resource investments required to explore the aforementioned variables and their effects on efficacy and structure–property relationships (SPRs).…”
mentioning
confidence: 99%
“…This limitation is common for methods involving rigid-body protein docking but not for molecular dynamics-based protocols: in such cases, we advise one to budget larger computational resources. 31 Furthermore, we showed that, even if sometime approximative, the DegraderTCM score, an energy estimation of the protein-binding moieties, can rationalize known degradation activity within PROTAC series, or at least distinguish active/ inactive pairs. When no reference pairs are available, one should investigate specific interactions established by the PROTAC in the TC model and compare them with X-ray structures of the protein-binding moieties for qualitative conclusions.…”
mentioning
confidence: 99%
“…Of course, we are aware that DegraderTCM may overlook huge protein conformational changes and struggle to model PPIs in less cooperative TCs. This limitation is common for methods involving rigid-body protein docking but not for molecular dynamics-based protocols: in such cases, we advise one to budget larger computational resources …”
mentioning
confidence: 99%
See 1 more Smart Citation